Efforts to empowerment the Community and Health Involunters Related to Non-Communicable Diseases (PTM) through Strengthening Posbindu - Hariyono; Ni Luh Ayu Megasari; Andri Setya Wahyudi (Institute of Computer Science (IOCS), 2022)
Morbidity and mortality of Non-Communicable Diseases (NCD) tends to increase in the last few decades in Indonesia, including at the global level. Posbindu as a Community-Based Health Effort (UKBM) which is held in accordance with the abilities and needs of the community. This Community Service aims to empower cadres in early detection of PTM risk factors which is carried out through several activities including the establishment of PTM Posbindu, training of cadres on PTM Posbindu, and continued monitoring of PTM risk factors. The results of community service obtained data that there were differences in the level of knowledge of cadres about PTM Posbindu before and after being given additional material. There was 1 cadre (6.25%) with a decreased score after the intervention, 13 cadres (81.25%) experienced an increase in post-test scores, and 2 cadres (12.5%) with a fixed score. The intervention given to the cadres was in the form of knowledge about the PTM Posbindu which consisted of the role of cadres in the implementation of the PTM Posbindu, the concept of the PTM Posbindu which included definitions, types of non-communicable diseases, targets, objectives, risk factors for PTM, and the implementation of Posbindu activities by cadres. The conclusion of this community service is the formation of PTM Posbindu in Plosobuden Village, Deket District. Besides. there was an increase in the knowledge and skills of cadres to carry out early detection of PTM risk factors such as measuring blood pressure, weighing weight, measuring height, calculating body mass index, conducting random blood sugar checks, measuring abdominal circumference and cadres were able to fill KMS FR-PTM , conduct counseling and referrals to first-level health facilities, as well as record and report the results of PTM Posbindu activities